Α-bisabolol enhances radiotherapy-induced apoptosis in endometrial cancer cells by reducing the effect of XIAP on inhibiting caspase-3. Issue 6 (10th June 2019) - Fang, Dongmei; Wang, Hongxin; Li, Min; Wei, Wenwen
Abstract : Endometrial cancer (EC) is one of the most common cancers in females. Although the diagnosis and treatment in early stages can greatly improve the survival rate of patients, the advanced EC still is lethal. Radiotherapy is widely used against EC, and it is a great challenge to find an effective way to overcome the resistance of EC during radiotherapy. α-bisabolol is a promising drug, which has already exhibited its anti-tumor effect in some malignancies. Here we reported that α-bisabolol could inhibit the proliferation of EC cells. It is also shown that their abilities of migration and invasion were effectively reduced by α-bisabolol. Furthermore, our results also demonstrated that α-bisabolol could improve sensitivity of EC cells in radiotherapy and further inhibited the growth of EC cells. By Western blot, we found the expression of matrix metalloproteinases-9 (MMP-9) and cyclin E were significantly decreased, which indicated that EC cells can be further suppressed by using α-bisabolol and radiotherapy. It is also demonstrated in our study that the rate of apoptotic cells is markedly increased in EC by using these two treatments. The significant decrease in X-linked inhibitor of apoptosis protein (XIAP) and increase in caspase-3 detected in our study suggested that the enhancement of apoptosis is mediated by XIAP/caspase-3 pathway, which was further confirmed by examining the downstream effectors of caspase-3, COX-2, PARP and cleaved PARP. In the present study, we demonstrated that α-bisabolol could enhance the sensitivity of EC cells to radiotherapy, which provide a novel alternative for overcoming radioresistance of EC cells and achieving a better outcome in radiotherapy.